Kejadian Berat Badan Lahir Rendah (BBLR) berdasarkan Faktor Prediktor Usia Kehamilan Dan Status Gizi Ibu - Khoirunnisa', Fania Nurul; Puspitasari, Indah; Yulianti, Indah; Nisak, Ana Zumrotun; Siagian, Dewi Sartika (Midwifery Care Journal, 2024)
Low birth weight (LBW) contributes about 60-80% of neonatal mortality. Factors such as gestational age and maternal nutritional status are among of the causes of LBW. Reducing infant mortality rate (IMR) is an essential indicator of a country’s success in improving public health. The aim of this study was to investigate the occurrence of LBW based on gestational age and maternal nutritional status at PKU Muhammadiyah Tegal hospital. This study was analytical and retrospective approach. The study population includes all mothers who gave birth at PKU Muhammadiyah Tegal hospital in July 2023 on 41 respondents. Data collection involves secondary data and statistically analyzed using chi square test. Result of the study found that from the respondents, 21 (51.2%) experienced preterm births (<37 weeks), while 22 (53.7%) were diagnosed with Chronic Energy Deficiency (CED) with Mid-Upper Arm Circumference (MUAC) < 23.5 cm. LBW occurred in 28 cases (68.3%). Chi-square analysis revealed a significant correlation between gestational age and LBW at Muhammadiyah Tegal PKU Hospital (p-value=0.010, OR: 7.773). Similarly, LBW occurrence based on maternal nutritional status also exhibited a significant relationship (p-value=0.004, OR: 15.000), indicating that pregnant women with CED have a 15 times higher risk of experiencing LBW compared to non-CED pregnant women